Verified Software: Theories, Tools, Experiments 5th International Conference, VSTTE 2013, Menlo Park, CA, USA, May 17-19, 2013, Revised Selected Papers - Cohen, Ernie; Rybalchenko, Andrey; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This volume constitutes the thoroughly refereed post-conference proceedings of the 5th International Conference on Verified Software: Theories, Tools, and Experiments, VSTTE 2013, held in Menlo Park, CA, USA, in May 2013. The 17 revised full papers presented were carefully revised and selected from 35 submissions. The papers address a wide range of topics including education, requirements modeling, specification languages, specification/verification case-studies, formal calculi, software design methods, automatic code generation, refinement methodologies, compositional analysis, verification tools, tool integration, benchmarks, challenge problems, and integrated verification environments.
Classifying and Solving Horn Clauses for Verification -- Static Analysis of Programs with Imprecise Probabilistic Inputs -- Effect Analysis for Programs with Callbacks -- Compositional Network Mobility -- Parallel Bounded Verification of Alloy Models by TranScoping -- Extending the Theory of Arrays: memset, memcpy, and Beyond -- An Improved Unrolling-Based Decision Procedure for Algebraic Data Types -- Program Checking with Less Hassle -- Verified Calculations. -- Preserving User Proofs across Specification Changes -- An Automatic Encoding from VeriFast Predicates into Implicit Dynamic Frames -- Automated Code Proofs on a Formal Model of the X86 -- Verification of a Virtual Filesystem Switch -- Verifying Chinese Train Control System under a Combined Scenario by Theorem Proving -- Formal Verification of Loop Bound Estimation for WCET Analysis -- Result Certification of Static Program Analysers with Automated Theorem Provers -- A Formally Verified Generic Branching Algorithm for Global Optimization.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).